Postural control after unexpected external perturbation: Effects of Parkinson's disease subtype - Beretta, Victor Spiandor [UNESP] (2019)
Different clinical subtypes of Parkinson's disease (PD) have long been recognized. Recent studies have focused on two PD subtypes: Postural Instability and Gait Difficulty (PIGD) and Tremor Dominant (TD). PIGD patients have greater difficulties in postural control in relation to TD. However, knowledge about the differences in reactive adjustment mechanisms following a perturbation in TD and PIGD is limited. This study aimed to compare reactive postural adjustments under unexpected external perturbation in TD, PIGD, and control group (CG) subjects. Forty-five individuals (15 TD, 15 PIGD, and 15 CG) participated in this study. Postural perturbation was applied by the posterior displacement of the support surface in an unexpected condition. The velocity (15 cm/s) and displacement (5 cm/s) of perturbation were the same for all participants. Center of pressure (CoP) and center of mass (CoM) were analyzed for two reactive windows after the perturbation (0–200 ms and 200–700 ms). The Bonferroni post hoc test indicated a higher range of CoP in the PIGD when compared to the CG (p = 0.021). The PIGD demonstrated greater time to recover the stable posture compared to the TD (p = 0.017) and CG (p = 0.003). Furthermore, the TD showed higher AP-acceleration peak of CoM when compared to the PIGD (p = 0.048) and CG (p = 0.013), and greater AP-acceleration range of CoM in relation to the CG (p = 0.022). These findings suggest that PD patients present worse reactive postural control after perturbation compared to healthy older individuals. CoP and CoM parameters are sensitive to understand and detect the differences in reactive postural mechanisms in PD subtypes.